2021
DOI: 10.3390/atmos12030374
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution in Moscow Megacity: Data Fusion of the Chemical Transport Model and Observational Network

Abstract: Comparisons of observational data obtained at the Moscow Ecological Monitoring network (MEM) with numerical simulations using a chemical transformation and transport model (SILAM—System for Integrated modeLling of Atmospheric coMposition) showed that the errors in determining the gaseous pollutant concentrations in the urban atmosphere have a more complex structure than those assumed under the conventional algorithms of data assimilation. These errors are statistically nonstationary; they show a pronounced diu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Several studies have demonstrated that atmospheric pollution affects medium and small-sized cities [3,4], even if the problem is more evident in large urban areas and metropolises [5,6], where the uneven distribution of emissive sources, the complex arrangement of buildings, and the composite photochemical reactions seriously complicate the assessment of the air quality level [7]. Moreover, the dense geometry of buildings and streets reduces the ventilation at the pedestrian level, limiting the exchange of momentum and mass between the canyons and the free atmosphere, further worsening the air quality and, consequently, the urban livability and human comfort [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that atmospheric pollution affects medium and small-sized cities [3,4], even if the problem is more evident in large urban areas and metropolises [5,6], where the uneven distribution of emissive sources, the complex arrangement of buildings, and the composite photochemical reactions seriously complicate the assessment of the air quality level [7]. Moreover, the dense geometry of buildings and streets reduces the ventilation at the pedestrian level, limiting the exchange of momentum and mass between the canyons and the free atmosphere, further worsening the air quality and, consequently, the urban livability and human comfort [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…1 ). Measurements at the stations are conducted using modern gas analyzers, which are regularly calibrated according to international standards and instructions of the World Meteorological Organization (WMO) developed for the Global Atmospheric Watch (WMO GAW) observation network [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The methods of utilizing heterogeneous measurement data are referred to as "data fusion" [36][37][38]. Data of different sources and types can complement and cross-validate each other.…”
Section: Introductionmentioning
confidence: 99%